Automation and the future of the welfare state: basic income as a response to technological change?. Issue 1 (1st January 2020) - Dermont, Clau; Weisstanner, David
ABSTRACT: Technology entrepreneurs have endorsed a universal basic income (UBI) as a remedy against disruptions of the work force due to automation. The advancement of information technologies could thus drastically reshape welfare state policy, but its impact on citizens' preferences about UBI is unexplored. We extend previous research on citizens' preferences showing a link between job automation and demand for redistribution to the case of UBI preferences. Using European Social Survey data in 21 countries, we find no association between risk of job automation and UBI support. Our findings suggest that UBI and redistribution preferences differ in two important ways: First, opinion formation about UBI is still ongoing. Second, demand for UBI is lower than demand for redistribution, and traditional supporters of redistribution are sceptical about an UBI. This points to the multidimensionality of policy preferences. Its universalistic nature could imply that UBI support is more culturally driven than traditional welfare policies.